Analysis Of The Effect Of Age On Medication Adherence With Oral Antidiabetes And Oral Antihypertension Drugs Using Pill Count Method: Analisis Pengaruh Usia terhadap Kepatuhan Minum Obat Oral Antidiabetes dan Oral Antihipertensi Menggunakan Metode Pill Count - Mas Ulfa, Ninik; Darmawan, Rizky (Akademi Farmasi Surabaya, 2021)
Compliance with taking medication is a problematic patients who get polypharmacy prescribing, this is because of the many drugs that must be consumed. As a result of the consumption of many drugs that cause sufferers of degenerative diseases are not compliant to take medication and health awareness decreases. This is not only experienced in elderly and geriatric patients but in adulthood also experience non-compliance with taking medication due to the many activities, lazy to take medication and also forget. This study was conducted to analyze the effect of age on adherence to taking oral antidiabetic drugs and oral antihypertensive drugs using the pill count method at the Regional Hospital of South Surabaya. The Pill Count method was chosen in this study with the aim of analyzing patient compliance in taking medication by calculating the remaining drug based on the rules of use and dosage when the patient returns to control. In addition, this study also aims to determine the effect of age on patient compliance in taking oral antidiabetic drugs and oral antihypertensive drugs. This research is descriptive observational with prospective data collection. Data analysis used descriptive and continued with statistical analysis using Chi-Square. The results of this study that adherence to take medication for elderly patients who received oral antidiabetic drug therapy obtained as much as 96.7% and 90% in adult patients. Compliance to oral antihypertension drugs in adult patients are 90% and 83.3% in elderly patients. Age does not effect compliance patients with Chi-Square analysis with p value = 0,301 and 0,448 > 0.05.